2014
DOI: 10.1002/jcp.24707
|View full text |Cite
|
Sign up to set email alerts
|

TGF‐β1 Suppresses Plasmin and MMP Activity in Flexor Tendon Cells via PAI‐1: Implications for Scarless Flexor Tendon Repair

Abstract: Flexor tendon injuries caused by deep lacerations to the hands are a challenging problem as they often result in debilitating adhesions that prevent the movement of the afflicted fingers. Evidence exists that tendon adhesions as well as scarring throughout the body are largely precipitated by the pleiotropic growth factor, TGF-β1, but the effects of TGF-β1 are poorly understood in tendon healing. Using an in vitro model of tendon healing, we previously found that TGF-β1 causes gene expression changes in tenocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 40 publications
2
29
0
Order By: Relevance
“…Collagenases such as Mmp1 target the structural collagens for degradation, whereas gelatinases such as Mmp2 and Mmp9 and membrane-bound MMPs, such as Mmp14, degrade smaller network collagens. Importantly, recent studies have shown that the expression and activity of MMPs are regulated by signals activated in response to mechanical forces, such as Itg and Tgfβ (Yu and Stamenkovic, 2000;Farhat et al, 2015). MMP misregulation also occurs upon tendon inflammation, and recent studies suggest that MMP inhibition can improve tendon repair (Bedi et al, 2010;Jelinsky et al, 2011;Farhat et al, 2012;Davis et al, 2013).…”
Section: Ecm and Collagen Fibril Assembly During Tendon And Mtj Maturmentioning
confidence: 99%
See 4 more Smart Citations
“…Collagenases such as Mmp1 target the structural collagens for degradation, whereas gelatinases such as Mmp2 and Mmp9 and membrane-bound MMPs, such as Mmp14, degrade smaller network collagens. Importantly, recent studies have shown that the expression and activity of MMPs are regulated by signals activated in response to mechanical forces, such as Itg and Tgfβ (Yu and Stamenkovic, 2000;Farhat et al, 2015). MMP misregulation also occurs upon tendon inflammation, and recent studies suggest that MMP inhibition can improve tendon repair (Bedi et al, 2010;Jelinsky et al, 2011;Farhat et al, 2012;Davis et al, 2013).…”
Section: Ecm and Collagen Fibril Assembly During Tendon And Mtj Maturmentioning
confidence: 99%
“…Injuries lead to excessive release of TGFβ owing to mechanical forcemediated activation of TGFβ (discussed below) and can cause fibrotic scarring of the tendon, thereby disrupting its function (Farhat et al, 2015). In one model, elevated TGFβ might overactivate MMPs, which in turn promotes further release of active TGFβ from the ECM as well as activating expression of Scx and Mkx and driving further ECM production.…”
Section: /Tgfb3mentioning
confidence: 99%
See 3 more Smart Citations